Antibacterial activity of fermented single-bulb garlic (Allium sativum L.) ethanol extract against ESBL-producing Escherichia coli - Mahyarudin Mahyarudin; Mardhia Mardhia; Delima Fajar Liana; Rangga Putra Nugraha; Ambar Rialita; Muhammad Syifa Irvandy (Universitas PGRI Pontianak, 2025)
Extended-spectrum beta-lactamase (ESBL)–producing Escherichia coli is a major cause of multidrug-resistant infections, posing significant challenges to antibiotic therapy. The search for natural antibacterial alternatives has led to growing interest in fermented single bulb Allium sativum (FSBAS), a thermally processed form of garlic with enhanced bioactive properties. This study aimed to evaluate the antibacterial activity of ethanol extracts of FSBAS against ESBL-producing E. coli isolates. FSBAS was produced by fermentation at 70°C for 35 days. FSBAS was extracted using maceration with 96% ethanol. Antibacterial activity was assessed using the disc diffusion method. This experiment consisted of four treatment groups i.e. extract concentrations of 25%, 50%, 75%, and 100%; and two control groups, namely the negative control (1% DMSO) and the positive control (amoxicillin–clavulanate, 30 µg/disc). The ethanol extract of FSBAS showed measurable antibacterial activity against ESBL-producing E. coli. The diameter of the inhibition zone increased proportionally with the extract concentration, with the strongest effect observed at 100%. Statistical analysis confirmed treatment groups with concentrations of 50%, 75%, and 100% showing no significant differences with positive control (p > 0.05). The FSBAS extract shows promising antibacterial potential against multidrug-resistant E. coli.